Proses Pembentukan UU: Studi Tentang Partisipasi Masyarakat dalam Proses Pembentukan UU - Author: Saifudin (Jurnal Hukum IUS QUIA IUSTUM, 2009)
Law-making is as a part of regulating state, is also demanded to transparency, participation and accountable. This will create legislation products that democratic and benefit for arrangement af state to bring into good governance with the 1945 Constitution as basic constitutional. In this research, I will examine one main problem: how public participation in legislative process? This research employs a sociological perspective , especially sociology of legislation. This reseach focuses on three legislations, i.e. Act on National Education System, Act on General Elections, and Act of Labor and the result shows as follows. Frist, the law-waking process in the reformation era has occurred changes in several aspects, such as representative institution, public interests, regulatory and law-making process. Second, public participation in the law-making process can be identified in several matters, such as people who participate, form of participation, method of participation, subject matter of participation, absorb of participation, and stages of participation. Third, public participation conducted in law-making process of the three Acts can affect in various law-making process. Therefore, it is expected that legislations enacted close to justice, compliance and legal certainty for society. Four, law-making process in the reformation era has opened public access and involved various political forces and society.Key word : People participation, process of acts formulation